2020
DOI: 10.3390/fire3020018
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fuel Treatments on Wildfire Behavior in North American Boreal Fuels: A Simulation Study Using FIRETEC

Abstract: Current methods of predicting fire spread in Canadian forests are suited to large wildfires that spread through natural forests. Recently, the use of mechanical and thinning treatments of forests in the wildland-urban interface of Canada has increased. To assist in community wildfire protection planning in forests not covered by existing operational fire spread models, we use FIRETEC to simulate fire spread in lowland black spruce fuel structures, the most common tree stand in Canada. The simulated tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Furthermore, the ICFME also produced some of the first field-based observations of structure ignition potential from crown fire (Cohen 2004); these observations have since been used to refine and validate models of structure ignition that have formed the foundation of safety zone size in the wildland-urban interface. Observations from the ICFME also provided validation data for new physically-based numerical models that couple fire and wind to allow more detailed investigations of the complex interactions that influence wildland fire behaviour (Linn et al 2012); such models continue to be used to augment existing observational evidence and explore important aspects in wildland fire management (Marshall et al 2020).…”
Section: Users [Text Box End]mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ICFME also produced some of the first field-based observations of structure ignition potential from crown fire (Cohen 2004); these observations have since been used to refine and validate models of structure ignition that have formed the foundation of safety zone size in the wildland-urban interface. Observations from the ICFME also provided validation data for new physically-based numerical models that couple fire and wind to allow more detailed investigations of the complex interactions that influence wildland fire behaviour (Linn et al 2012); such models continue to be used to augment existing observational evidence and explore important aspects in wildland fire management (Marshall et al 2020).…”
Section: Users [Text Box End]mentioning
confidence: 99%
“…Although commonly applied in montane forests of western North America, fuels management in crown-fire dominated boreal forests is a challenging balance between reducing crowning potential through fuel reduction (i.e., overstory thinning) without increasing surface fire intensity (through increased overall fuel dryness and increased surface wind). While the original fuel typing in the FBP System was not readily adaptable to studying the impact of fuels management on fire behaviour, a significant emphasis of the new generation of the FBP System (currently under development) will focus on a more structural definition of fuel complexes that allows users to consistently evaluate the effects of stand manipulations (Marshall et al 2020).…”
Section: Users [Text Box End]mentioning
confidence: 99%
“…There is numerous wildfire simulation modeling research work in the literature, addressing various aspects of this phenomenon. An example of more recent studies can be found in [15,[94][95][96][97].…”
Section: A Wildfire Simulatorsmentioning
confidence: 99%
“…Furthermore, the interaction of a wind-driven elongated fire front with the atmosphere introduces complexities for fire spread [16] that may have implications for firebrand transport compared to point-source stationary fires. Similarly, laboratory methods of firebrand production provide extremely valuable insights on structure ignition processes, but the impact of mitigation measures such as forest fuel reduction on firebrand production and transport in conifer crown fires remain largely limited to physics-based modelling [17].…”
Section: Introductionmentioning
confidence: 99%